Community Empowerment of Islamic Boarding Schools Through Introspection Surveys to Realize Healthy Islamic Boarding Schools at Nurul Hidayah Islamic Boarding Schools - Irma Prasetyowati; Ida Srisurani Wijiastuti; Zulfa Mazida (Faculty of Public Health, University of Jember in collaboration with PERSAKMI, 2022)
Islamic boarding school is a place where students gather in one room such as sleeping, eating, studying and using shared bathrooms so that it becomes a risky place for disease transmission. The activity stages started from setting priorities for existing problems using the USGF (Urgency, Seriousness, Growth, Feasibility) matrix and next stage conducted an introspective survey. Diarrhea is the first priority health problem in the Nurul Hidayah Islamic boarding school. The results of the introspective survey stated that all students did not wash their hands with soap before and after eating and defecating or urinating, all students also often consumed food from outside. Based on observation, the Nurul Hidayah Islamic boarding school did not have a handwashing area yet, a closed trash can, and a Poskestren. Empowerment of the pesantren community through an Mawas Diri survey resulted in setting priorities for health problems in the Nurul Hidayah Islamic boarding school environment, namely diarrheal disease. From the results of filling in the introductory survey instrument, behavioral and non-behavioral (enivornment and policy) factors will be obtained that were at risk of disease transmission, especially diarrhea.